Isolasi dan Identifikasi Senyawa Antioksidan dari Ekstrak Benalu Teh (Scurrula oortiana (Korth) Danser) - Partomuan Simanjuntak; Titi Parwati; Lisya Evy Lenny; Swasono R. Tamat; Retno Murwani (JURNAL ILMU KEFARMASIAN INDONESIA, 2004)
The leaves of tea benalu (Scurrula oortiana (Korth) Danser) were extracted with nhexane, ethyl acetate, methanol, and water respectively. The antioxidant activities were measured using 1,1-diphenyl-2-picrylhidrazyl (DPPH) methods. The result showed that the isolated compound has scavenging effect with IC50 92.22 ppm. Identification by interpretation of ultraviolet, infrared, and nuclear magnetic resonance spectra showed that the isolated compound was cathecin.